La auditoria financiera como herramienta para mitigar reiesgos en la sostenibilidad economica de las PYMES en Colombianas (2021)
This article addresses the importance of financial auditing as a tool to mitigate the risks in the economic sustainability of SMEs, highlighting the main aspects of the application of the audit, As support in the NIAS, taking it to the specific level of SMEs, in such a way that allows to clearly identify how all the benefits obtained by applying in search of sustainability and continuous contribution to the country's economy. It is important to highlight that these companies in Colombia represent an important percentage in the economic sector and that they are currently one of the main drivers of the national heritage. Therefore, it is important that they remain aligned with international standards. As a methodological support of this qualitative type, as more descriptive research is carried out supported by the most relevant opinions and concepts presented by several authors that expand consistent and effective information about the economic effect that the use of audits can represent in their business models, achieving highlight the importance of NIAS in the entire process of business growth. In addition, by performing regular audits on its deliveries, future risks can be identified, making it sustainable and adaptable over time. Finally, through the use of simple questionnaires, it is possible to graphically determine how far companies are from that reality and willing to make adjustments in their business models, to adapt to the changes presented by current regulations.